Assessment on the Citizenship Education Learning Process (PKn) MI/SD Level - Fitri Khoiriyah Sayidah Harahap; Nurul Handini; Siti Fadilla; Annisa Ramadhani (Yayasan Zia Salsabila, 2022)
This study aims to find out information on civics assessment in SD/MI. The research used is a descriptive method with a qualitative approach and a causal-effectual analysis model using a rational approach based on the results of a literature review (literature review). Literature study is an activity with the method of collecting data from various sources, both from books, journals or articles that are in accordance with the subject matter. The results of the study show that the Citizenship Education Assessment of SD/MI is an activity of collecting reports and using information about student learning outcomes in civics subjects by applying the principles of assessment, continuous implementation, authentic, accurate and consistent evidence. Assessment or called assessment is a process of gathering information to measure the results of knowledge, attitudes and skills of students using the principles of assessment.